PENGARUH BRAND IMAGE DAN CELEBRITY ENDORSER TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH (STUDI PADA KONSUMEN WARDAH KOTA SEMARANG) - Ayu Laksmi Dara; Apriatni Endang Prihatini (Jurnal Ilmu Administrasi Bisnis, 2019)
Cosmetics today have become a mandatory requirement for women to increase self-esteem. Wardah is one of Indonesia's local brands that has distribution centers not only in Indonesia, but also in Malaysia due to high consumer demand in several major cities. However, some of Wardah’s outlets in Semarang City have a decrease in number. This study aims to determine  the effect of  brand image and celebrity endorser on purchasing decisions of Wardah’s products. This type of research is explanatory research and sampling uses nonprobability sampling techniques, purposive sampling method. Data collection using questionnaires and google form. The sample is used amount 100 respondents using Wardah’s products in Semarang City. This study uses quantitative and qualitative analysis with validity, reliability, correlation coefficients, coefficient of determination, simple and multiple regression, significance of t test and F test. The results of the study show that the variables of brand image and celebrity endorser have an effect on purchasing decisions. The variable correlation coefficient of brand image and celebrity endorser on purchasing decisions has a strong enough relationship, The determination coefficient of brand image on purchasing decision variable is 27,5%, and the determination coefficient of the celebrity endorser variable on purchasing decisions is 20,9%,